guys please help me with this question and whoever will give me the answer I will mark them as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d5a/5775ef267cf19ab7f0a63dee66ab1c74.jpg)
Answers
Answered by
1
Step-by-step explanation:
that's your answer..
happy to help!
Attachments:
![](https://hi-static.z-dn.net/files/df9/575f029020a5b95b9730b3026b251e3c.jpg)
Answered by
0
Step-by-step explanation:
L.H.S. = (cosec A – sin A)(sec A – cos A). sec2 A
= (1/sin A – sin A). (1/cos A – cos A). 1/cos2 A
= (1 – sin2 A/sin A) × (1 – cos2 A/cos A) × 1/cos2 a
= cos2 A/sin A × sin2 A/cos A × 1/cos2 A
[∵ (1 – sin2 A) = cos2 A]
[∵ 1 – cos2 A = sin2 A]
= sin A/cos A = tan A
= R.H.S.
Hence proved.
Similar questions